(untitled) (South East Asia Journal of Public Health, 2013)
The aim of this study is to determine correlations among anthropometric parameters, systolic and diastolic blood pressure in hypertensive subjects in Lahore, Pakistan. A total number of 510 subjects (204 males and 306 females) of age between 25-87y were included in the study. The subjects were divided into pre (n=139), stage 1 (n=193) and stage 2 of hypertension (n=178) following JNC VII criteria (2003). Following the World Health Organization (WHO) cutoffs for Asians, about 13.7% of our sample population was found to be overweight and 76.7% was obese, 54.1% had waist to hip ratio (WHR) greater than 1. It was found that females develop hypertension in earlier age than males. Body Mass Index (BMI) was greater in females while WHR in males. No significant difference was observed in BMI and WHR among the prehypertension (preHTN), stage 1 and stage 2 subjects. A significant asso-ciation was found between systolic blood pressure (SBP) and WHR in pre-hypertensive subjects (r=0.168). A posi-tive significant correlation of diastolic blood pressure (DBP) was found with WHR (r=0.212) and BMI (r=0.17) in prehypertensive stage. In multiple regression analysis when SBP was a dependent variable, age and BMI was deter-minant in preHTN, while only age was in stage 2. When DBP was a dependent variable, WHR was predictor in preHTN and age in stage 2. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15939 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 22-27